The effect of technology disruption on organisational health: mediating effect of competence adequacy and moderating effect of innovation capacity and competence building - Nair, Hari AP (2016)
As a world’s fastest growing telecommunication market, India is undergoing evolutionary changes in telecommunication technologies. Rapidly changing communication technology has been posing innumerable challenges to the telecommunication companies in India for adequate skill availability and at the same time significantly changing competence requirements. The recognition of competence adequacy as a key factor to sustain organizational health in an increasingly competitive telecommunication sector has opened up several possibilities of competence based research. The study examined the inverse effect of technology disruption on competence adequacy and subsequently on the organizational health. Further, the organization’s intervention to competence building and innovation capacity was also put through the moderating tests as balancing factors. Knowledge Evolution Theory underpins this study framework to highlight the competence issues caused by technology disruption. This quantitative study was conducted in India among four leading Telecommunication firms. An online questionnaire was administered to managers from the firms who were selected using stratified random sampling. The eight hypotheses of this study were tested with Structural Equation Modelling using AMOS software. The results of the study found significant positive effects of competence adequacy, innovation capacity and competence building on organisational health. Secondly, technology disruption was found to have significant negative relationship with both competence adequacy and organisational health. In addition, the interaction of competence building and innovation capacity on the path of technology disruption and competence adequacy significantly moderated the relationship and finally, competence adequacy was found to have a significant mediating effect on the relationship between technology disruption and organisational health. The study provides new directions to the practising human resource professionals to improve the competence adequacy in high technology industries especially among telecommunication companies. The results of the study also highlights the widening technology skill gap present in telecommunication industry in India. The findings of this study also have pointed out the importance of innovation capacity as balancing factor in technology firms in the wake of evolutionary changes in telecommunication technology.